2008
DOI: 10.1111/j.1600-0579.2007.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in access to education and healthcare

Abstract: The burden of disease is borne by those who suffer as patients but also by society at large, including health service providers. That burden is felt most severely in parts of the world where there is no infrastructure, or foreseeable prospects of any, to change the status quo without external support. Poverty, disease and inequality pervade all the activities of daily living in low‐income regions and are inextricably linked. External interventions may not be the most appropriate way to impact on this positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
(20 reference statements)
0
27
0
1
Order By: Relevance
“…A small cross sectional study in people with intellectual disability found a high prevalence of dental caries and toothlessness 15 ; Nunn et al found a lack of access to adequate training in the dental needs of groups with disabilities. 16 In a cross sectional study, constipation was significantly correlated with lack of mobility, cerebral palsy, the use of anticonvulsants, benzodiazepines, proton pump inhibitors, and refusal to eat. w10 Constipation may remain unreported and undetected for a long time and may cause severe problems such as ileus.…”
Section: Secondary Health Conditionsmentioning
confidence: 99%
“…A small cross sectional study in people with intellectual disability found a high prevalence of dental caries and toothlessness 15 ; Nunn et al found a lack of access to adequate training in the dental needs of groups with disabilities. 16 In a cross sectional study, constipation was significantly correlated with lack of mobility, cerebral palsy, the use of anticonvulsants, benzodiazepines, proton pump inhibitors, and refusal to eat. w10 Constipation may remain unreported and undetected for a long time and may cause severe problems such as ileus.…”
Section: Secondary Health Conditionsmentioning
confidence: 99%
“…Therefore, the question of how well dental schools educate future dentists is still open. Moreover, there is a controversy about which level of educational carrier (pre-, post-doctoral or both) is necessary to prepare dental students in the management of patients with disabilities (9).…”
Section: Introductionmentioning
confidence: 99%
“…We can conclude that the notion of caring as the hallmark of a stereotyped female dentist appears in our results, and that statistics imply that female dentists may outnumber their male colleagues in the foreseeable future (Nunn et al, 2008). It is quite possible that, for good or bad, women will soon be the dentist norm and their male colleagues will no longer "get away with" for example being authoritarian or leave for the nurse to clean up the workplace.…”
Section: Ambiguity Blurring and Gender-power Relationsmentioning
confidence: 55%
“…Even though statistics are somewhat incomplete, approximately 36 percent of the dentists in these regions were women in the year 2000 (Zillén & Mindak, 2000). The number of female dentists is expected to rise due to a recent, marked, shift in the gender distribution of the dental student population in Western Europe and North America; where the majority of the students now are women (Nunn et al, 2008). After a dip in the 1980-90s characterised by few applicants per place, the dentistry programme is re-establishing its status as one of the most popular higher educational programmes in Sweden, which has led to strict admittance requirements.…”
Section: Introductionmentioning
confidence: 99%